Study of Reproductive Aspects of Fish Cyprinidae Family and Poeciliidae Family in Lake Batur Waters Area, Bali - Winni Anugrah Hani; Nyoman Dati Pertami; I Wayan Darya Kartika (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
This study aims to determine the reproductive characteristics of the Cyprinidae and Poeciliidae families in Lake Batur, including gonad maturity stage, gonadosomatic index, and sex ratio. Sampling was carried out from November to December 2021. This study uses descriptive and quantitative methods, with purposive sampling at three station points. The fishing gear used is a gill net with sizes of 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0 inches. Determination of the gonad maturity stage of the gonads is determined morphologically, which includes observations on the color, shape, and size of the gonads. The gonad maturity stage III and IV was analyzed with the gonadosomatic index and sex ratio. The fish samples total 147 individuals: 54 from the Cyprinidae family and 93 from the Poeciliidae family. Cyprinidae family fish samples are Barbodes binotatus and Barbonimus gonionotus. Poeciliidae family fish samples are Xiphophorus hellerii and Poecilia reticulata. gonad maturity stage of the cyprinidae family in Barbodes binotatus obtained I -IV and Barbonimus gonionotus fish obtained all stages I-V, while the poeciliidae family Xiphoporus hellerii at all stages IV and Poecilia reticulata only found I-IV, the average of gonadosomatic index of female cyprinidae and poeciliidae is higher than males, and spawning time occurs in November and December (rainy season). The sex ratio of the Cyprinidae family in Barbodes binotatus is unbalanced, while in the Poeciliidae family, the sex ratio of Xiphophorus hellerii is balanced.